PENGARUH PENGGUNAAN E-WALLET DAN LITERASI KEUANGAN TERHADAP PERILAKU PEMBELIAN IMPULSIF PADA MAHASISWA USN KOLAKA (Program Studi Akuntansi 2021-2024) - Annisa, Annisa; Triani, Neks; Bustang, Bustang (Jurnal Daya Saing, 2025)
The purpose of thisresearch is to study the use of E-Wallets and financial literacy and whether they affect students' impulsive buying behavior. Using a quantitative approach and processed using SPSS 25. This study indicates that the use ofE-Wallets along with financial literacy influences impulsive buying behavior. The R square value is0.578, which indicates that the impact of E-Walletusage and financial literacy on impulsive buying is57.8%, while the remaining42.2% is determinedby other variables. Keywords: Capital Structure, Company Growth, Company